Microfibrillated cellulose enhancement to mechanical and conductive properties of biocompatible hydrogels. (1st February 2019) - Lin, Fengcai; Zheng, Ruting; Chen, Jianwen; Su, Wenmin; Dong, Biying; Lin, Chensheng; Huang, Biao; Lu, Beili
Highlights: Ionically crosslinked and in situ polymerization strategy were introduced. TOMFC facilitated the formation of more compact 3D network structures of hydrogels. TOMFC significantly enhanced mechanical and electrical properties of hydrogels. The hydrogels displayed tunable swelling properties and good biocompatibility. Abstract: A combination of conductive polymer with natural biomass is an ideal alternative to the classical conductive materials. In this study, PPy/SA/TOMFC composite hydrogels were fabricated by incorporation of TEMPO-oxidized microfibrillated cellulose (TOMFC) into the alginate-based matrix along with the in situ polymerization of pyrrole monomer. It was found that the mechanical and conductive properties of the composite hydrogels were associated with the concentration of TOMFC, which facilitated the formation of more compact 3D network structures and the growing of PPy conductive network. The mechanical properties of the synthesized hydrogels were significantly enhanced by incorporation of higher amount of TOMFC. In addition, with the introduction of 5.0 wt% TOMFC, the electrical conductivity of composite hydrogels could be ten times higher than that of PPy/SA hydrogels. Moreover, the obtained PPy/SA/TOMFC hydrogels exhibited tunable swelling properties and good biocompatibility, making them promising candidates for the use as biomaterial.